2013
DOI: 10.1016/j.jue.2012.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Do governments tax agglomeration rents?

Abstract: Using the German local business tax as a testing ground, we empirically investigate the impact of firm agglomeration on municipal tax setting behavior. The analysis exploits a rich data source on the population of German firms to construct detailed measures for the communities' agglomeration characteristics. The findings indicate that urbanization and localization economies exert a positive impact on the jurisdictional tax rate choice which confirms predictions of the theoretical New Economic Geography (NEG) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 55 publications
3
27
1
7
Order By: Relevance
“…We show that, under mild conditions, the central city typically levies a higher business tax than suburban governments, a result that is backed up by the empirical literature (see Koh et al, (2013) and Brülhart et al (2015) for references). The reason for this is that consumers working in the central city need not reside therein, which incentivizes the central city's government to practice tax exporting, the extent of which depends on the relative size of jurisdictions and the intensity of agglomeration economies.…”
Section: Introductionsupporting
confidence: 67%
“…We show that, under mild conditions, the central city typically levies a higher business tax than suburban governments, a result that is backed up by the empirical literature (see Koh et al, (2013) and Brülhart et al (2015) for references). The reason for this is that consumers working in the central city need not reside therein, which incentivizes the central city's government to practice tax exporting, the extent of which depends on the relative size of jurisdictions and the intensity of agglomeration economies.…”
Section: Introductionsupporting
confidence: 67%
“…7 Count models of firm location have subsequently been estimated by List (2001), Guimaraes et al (2003) and Holl (2004). 8 In a related strand of recent research, Charlot and Paty (2007), Jofre-Monseny and Solé-Ollé (2010, 2012), Koh and Riedel (2010), Jofre-Monseny (forthcoming) and Lü thi and Schmidheiny (2011)) have found that local tax rates are positively correlated with measures of local agglomeration.…”
Section: Literature Backgroundmentioning
confidence: 99%
“…Neighbors are thereby defined as two jurisdictions that share a border (e.g., Heyndels and Vuchelen, ; Geys, ; Rincke, ) or are within a certain Euclidian or travel distance from each other (e.g., Buettner, , 2003; Bosch and Solé‐Ollé, ; Brett and Tardiff, ). In a similar vein, the inverse of the distance between jurisdictions is often invoked to approximate the strength of the assumed competitive relation between them (e.g., Brueckner and Saavedra, ; Charlot and Paty, ; Koh, Riedel, and Böhm, ). Such distance‐based criteria can be justified by the fact that proximity is important for the dissemination of information—certainly at the local government level (Allers and Elhorst, )—and is linked to relocation decisions of both individuals (Day, ) and firms (van Dijk and Pellenbarg, )…”
Section: Literature Overview and Hypothesesmentioning
confidence: 99%